STRATEGI PENGEMBANGAN KOPI ROBUSTA DI KABUPATEN MERANGIN - M. Rialdi Syaputra (Khazanah Intelektual, 2021)
Sumatran Merangin Robusta Coffee has a plant area currently reaching 11,002 hectares. Coffee farming is one of the main livelihoods of the population in three districts, namely Jangkat, Sungai Tenang and Lembah Masurai sub-districts. The development of coffee commodities is very important in order to increase productivity and competitiveness. Regional government political support through various regulations aimed at creating various forms of convenience for agribusiness activities which are expected to boost commodity competitiveness. Therefore, it is necessary to formulate a policy strategy for the development of regional superior commodities, especially coffee, so that in the future the development of the coffee commodity can be more developed and product competitiveness is more competitive. This study aims, to describe the existing conditions of robusta coffee farming, and the strategy and design of the Robusta Coffee Farming Development program in Merangin Regency, the development of robusta coffee in Merangin Regency. The method used in this research is SWOT analysis and QSPM (Quantitative Strategic Planning Matrix). The results show that the majority of robusta coffee farmers in Merangin Regency are of productive age, most of whom have their own land with an area of ​​1 to 3 hectares. The market structure that is formed is an imperfect competitive market. Then the strategy for the development of robusta coffee farming in Merangin Regency is through the downstreaming of robusta coffee farming so that it can increase the added value of coffee-based products, improve farming technical skills to improve the quality of processed products based on robusta coffee and empower members and farmer groups. The priority of designing a robusta coffee development program in Merangin Regency is directed at increasing the capacity of robusta coffee farmers to be able to face competition, developing access to coffee marketing through product promotion, growing investor interest in and outside the region to develop downstream coffee-based products and building supporting infrastructure at centers. Robusta coffee production in Merangin Regency.